The syndemic, an opportunity for homeless people in Chile - Urrutia, Pedro (2022)
Introduction: The research analyzes the experience of people who live on the street, and that due to the syndemic produced by the SARS-CoV-2 virus in the world, in particular in the city of Temuco in Chile, they have had to live within hostels and/or shelters, which were from being temporary to permanent devices. Objective: Understand the ways in which people in street situation appropriate the spaces of a hostel or shelter, which in an unplanned way and without being the objective of these, begin to carry out therapeutic processes, and recognize the practices in their daily life. Method: Qualitative research, with an ethnomethodological perspective. An intentional sampling is considered, using as information production techniques, the in-depth interview and participant observation. Result: It accounts for the changes in personal aspects, in the processes of connection and motivation to maintain their improvements for as long as possible, leaving the consumption of alcohol and/or drugs and resuming their health processes, taking responsibility for the spaces, making decisions and developing routines that were not planned. Conclusions: Generating spaces realizes us that people who live on the street do not enter their harmful behaviors into this space, they agree that not having to go out on the street does not make consumption necessary of alcohol and/or drugs, that they can project their life beyond the street, that the processes of self-exclusion or isolation are demolished when they share their experiences with others and they found an opportunity with the syndemic.